Aerofotogrametria por meio de Vants: análise da viabilidade no levantamento planialtimétrico - Lima, Pedro David Rodrigues (Universidade Federal Rural do Semi-Árido, 2018)
The use of unmanned aerial vehicles (UAVs) used in the study of digital photogrammetry is a tool that has been growing significantly in the last years, mainly in engineering, where it is used to obtain the necessary information for the execution of projects, providing a smaller time of execution and cost, as well as an adequate quality in obtaining data. One of the applications related to the use of aerial images performed by VANTs in engineering is the acquisition of planialtimetric data, a technique widely used by topography in the acquisition of information about a certain region of the earth's surface. Therefore, this study aims to analyze the feasibility of the use of UAVs in the planialtimetric survey and in the cartographic production of land surface. For this, a quantum mapper was used for the acquisition of aerial photographs, as well as the software: QGIS, used in the production of maps, and Agisoft Photoscan, used for the processing of the raw data generated by the VANT. As a result of the image processing, a Digital Surface Model (MDS), Digital Terrain Model (MDT), Ortomosaic and Level Curves were obtained, which were used for quantitative and qualitative analyzes of the terrain. Finally, it was verified that the UAV together with the photogrammetry has a viable job in topographic and planialtimetric surveys, since the errors found were considerably small, thus giving greater reliability in the generated products.
Keywords: Veículo aéreo não tripulado; Fotogrametria; Curva de nível; Topográfico; Unmanned aerial vehicle; Photogrammetry; Level curve; Topographic; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA